Modelling Fire Severity and Evacuation in Tunnels - Mozer, Vladimir (Communications - Scientific letters of the University of Zilina, 2013)
Adequate design methods and tools are vital to any construction project, especially when its complexity and value are high. Tunnels, road or railway, are a good example of such structures. This paper deals with the topic of computer modelling utilization in the design and evaluation of fire safety in tunnels. The capabilities of selected software – Fire dynamics simulator + Evac – are demonstrated on a practical example – Tunnel Lucivna in the Slovak Republic. In this example case, both fire and evacuation modelling is used in conjunction to assess the overall fire safety of the tunnel. The results show the effects of fire on the tunnel structure as well as the persons inside the tunnel trying to evacuate.